SUBSIDIZING AGRICULTURAL RISKS: TRENDS AND OPPORTUNITIES - Maria COJOCARU; Iulia CAPRIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the issue of subsidizing agricultural risks in Moldova. The data were collected from the National Bureau of Statistics of the Republic of Moldova, the Agency for Payments and Intervention for Agriculture, National Commission of Financial Market,insurance companies, and various studies on the topic. The study was based on the following methods: monograph, analysis, synthesis, time series analysis, trend analysis, graphical method, etc. It was concluded that agricultural insurance represents a real mean for crop protection and for the investments made in this sector. Agricultural risk subsidy programs implemented in Moldova so far can be considered inefficient and unattractive for farmers. It requires a radical rethinking of the policy of subsidizing agricultural risks.